A facile approach for the determination of degree of deacetylation of chitosan using acid-base titration. Issue 7 (July 2022) - Dutta, Joydeep; Priyanka,
Abstract: Several spectroscopic techniques such as nuclear magnetic resonance (NMR), UV-visible, Fourier transform infrared (FT-IR), etc. have been already used for the determination of degree of deacetylation (DD) of chitosan. These techniques involve the interpretation of spectral data apart from sample preparation for obtaining DD of chitosan. In addition, inaccurate interpretation of data sometimes misleads researchers to get an exact value of DD of chitosan. Among them, NMR is an excellent technique for the estimation of DD of chitosan but expensive and not found easily in every research laboratory. On the other hand, titrimetric methods have been employed by many researchers for determining the DD of chitosan but these existing methods involve many complex calculations, which do not always give accurate results. Moreover, few of the acid-base titration methods are little complicated for execution. Therefore, in this present study, we adopted a very handy and simple acid-base titration method with a new approach and proposed a new equation facilitating the ease of calculation that is not reported elsewhere for the determination of DD value by observing the net volume of NaOH consumed for the complete neutralization of protonated amino groups (-NH3 + ) of chitosan describing the novelty of the work. All the DD values (77.04 ± 1.36; 81.71 ± 1.73; 91.68 ± 1.42 for CS1, CS2, and CS3 respectively) obtained for various chitosan samples were in good agreement with the reported DD values (>75%, >80%, and >85% for CS1, CS2, and CS3 respectively) mentioned in the specifications of chitosan samples supplied by the manufacturer. Finally, the experimental DD values were further validated with the DD values (77.39%, 81.64%, and 90.5% for CS1, CS2, and CS3 respectively) obtained from the interpretation of 13 C-NMR spectral data and all the experimental DD values were consistent with the DD values as calculated based on NMR spectra. Graphical abstract: Image 1 Highlights: The acid-base titration method with a new approach reported in this article for the determination of degree of deacetylation of chitosan provides an accuracy, reproducibility, and reliability. In addition, the reported method with a new approach is very convenient as compared to other existing methods to determine the degree of deacetylation of chitosan. The newly introduced equation to estimate degree of deacetylation of chitosan is very simple and convenient. The DD values of chitosan obtained by the acid-base titration method are perfectly validated based on 13 C-NMR data. Abstract : Degree of deacetylation, Chitosan, Acid-base titration, New equation, Ease of calculation, 13 C-NMR.